The equal and inviolable dignity of the human person as the foundation of the national and international juridical order (Prudentia Iuris, 2017)
The present work develops two fundamental theses. First, it treats the equal and inviolable dignity of the human person as a starting point and arrival of all theorizing and practice of Law. Finally, as a second thesis, it develops the need to deepen in the anthropological, philosophical and theological foundations of the dignity of the human person, an authentic moral patrimony of humanity that must be preserved and grounded.
Keywords: Human person; Dignity; Natural Law; Legal order